Changes in cognitive functioning in sick-listed participants in occupational rehabilitation: A feasibility study. (1st November 2016) - Johansen, Thomas; Skjerve, Arvid; Jensen, Chris; Dittrich, Winand H.; Øyeflaten, Irene
Abstract: Background: Individuals on long-term sick leave attending occupational rehabilitation often complain about impairments in cognitive functions such as memory and attention. Knowledge of cognitive functioning in these individuals is limited. Such knowledge is clinically relevant for improving occupational rehabilitation programmes. Objective: The aims of this feasibility study were to assess the methodological design and to investigate changes in memory and attention on participants during occupational rehabilitation. Methods: Individuals attending occupational rehabilitation ( n  = 28) and individuals working full time ( n  = 25) matched for age, gender, and education participated. The two groups were administered cognitive tests targeting memory and attention and self-reported questionnaires at pre-test and post-test. Outcome measures were speed and accuracy of responses on the cognitive tests and self-reported work ability, subjective health complaints, and symptoms of depression and anxiety. Results: In total, 35% of all invited participants agreed to take part and 93% of these also completed the second test. The mean gain scores in the intervention group were significantly higher than in the control group in response latency on simple and choice reaction time and errors in spatial working memory. Conclusion: The results of this study indicate that the motivation of participants to complete testing was high. Improvements in memory and attention were evident in rehabilitation participants indicating that rehabilitation may have an effect on cognitive functions.